Hittite intervention in the northern Syrian kingdoms (Yamhad,Alalakh) 1600-1200 B.C - عبد الحق حسان; صقر ريم سهيل (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research defines an ancient kingdom adjacent to the kingdoms of the ancient Syrian region. It is the Hittite Kingdom in the modern Bronze Age 1600-1200 BC by defining its expansionist policy to achieve its ambitions to control the potential and resources of the northern Syrian kingdoms; Yamhad / Aleppo ̸ Alalakh By highlighting the potential and wealth and economic and geographic importance of tow kingdoms in relation to the Hittites who took from the heart of Anatolia the center of their empire, and to emphasize the close dialectical relationship between the economy and geography with the political side as a magnet and a key driver determines policies Foreign kingdoms and State.